Solanum hirtum as a host plant for Mechanitis menapis menapis (Lepidoptera: Ithomiinae) in Colombia - GIRALDO-S., CARLOS EDUARDO; URIBE-S., SANDRA I. (Revista Colombiana de Entomología, 2010)
Specimens of Mechanitis menapis menapis (Lepidoptera: Nymphalidae: Ithomiinae) were collected from three localities in the Colombian Andes. Eggs and larvae found on the host plant were collected and studied under laboratory conditions. The plant on which the immatures were found was identified as Solanum hirtum, which represents a new host plant record for Mechanitis menapis in Colombia. The observations presented contribute to an understanding of the host plants of Neotropical diurnal butterflies, and specifically the Ithomiinae, for Colombia.